The neuroactive potential of the elderly human gut microbiome is associated with mental health status - Paulina Calderón-Romero; Benjamin Valderrama; Thomaz F. S. Bastiaanssen; Patricia Lillo; Daniela Thumala-Dockendorff; Gerard Clarke; John F. Cryan; Andrea Slachevsky; Christian González-Billault; Felipe A. Court (PLoS ONE, 2026)
Ageing is usually associated with physiological decline, increased mental health issues, and cognitive. deterioration, alongside specific changes in the gut microbiome. However, the relationship between the neuroactive potential of the gut microbiome and mental health and cognition among the elderly remains less explored. This study examines a cohort of 153 older Chilean adults with cognitive complaints, assessing anthropometric data, mental health via five distinct tests, and gut microbiome composition through 16SV4 sequencing. Our findings reveal associations between anthropometric factors and depression scores in mental tests of participants with their gut microbiome composition. Notably, depression was associated with changes in the abundance of Lachnospiraceae Eubacterium xylanophilum group and Fusobacteriaceae Fusobacterium . Additionally, bacterial pathways involved in metabolising neuroactive compounds such as tryptophan, short-chain fatty acids, p-cresol, glutamate, and nitric oxide were associated with participant age, sex, and cognitive performance. Moreover, participants’ sex was associated with the neuroactive potential of specific bacteria, suggesting a role of the gut microbiome in sex-related mental health differences in the elderly. Altogether, this study provides the first evidence from a South American cohort linking the inferred neuroactive potential of the gut microbiome to cognitive and psychological function in older adults with cognitive complaints, offering novel insights into microbiota-based mechanisms that may contribute to mental health and ageing.